Sobre a imagem-movimento ou as cartas que enderecei a Deleuze - Madeiro, Elen Naiara Batista (2015)
This work aims to study the taxonomy of film images made by Deleuze, considering the cinema as an experience that builds their own senses. This research has come a way that went through a cinema that makes you think and met a cinema thinking itself. He also found conceptual revolutions, revisiting perceptions, feelings and actions and jeopardizing a consciousness anchored in a subject. My work is not intended to dictate truths about the work of Deleuze in a matter, nor about any other. I allow myself to use unpretentious words, those that do not crave status of truth, those that do not imprison the senses, those that mobilize partners and admit the possibility of not being. It is a work that aims, based on my experience, open up a dialog field and possible understandings with these author and work as enigmatic as seductive. Expose a way of understanding, a peculiar significance created to try such a book does not appear to be a job fair for an author of such impact and fame, even more coming from a master's student at a public university in the capital of the smallest state in Brazil. But it is just the work that I propose, is just what will be found below. I signal the difficulty in dealing with the text and find partnerships and references, mostly within psychology. During the research I discovered that the affliction are not only mine, and therefore fills this work with collectivity and complicity. Along with the difficulties and shortage of references and partnerships is that are created escapes. In order that the grace not not transmute itsef in paralysis, amid conversations, meetings and guidelines was that I (a self multiple, crossed by diverse forces) chose the format of letters to give vent to all the insecurities and powers that inhabit this search.